Faculty turnover at the Mindanao State University, Marawi City - Villamater, Luzviminda (Abainza) 1937-; Mindanao State University, Marawi City ([Quezon City s.n.], 1973)
An open-ended questionnaire, exit personal interviews, and records at the MSU Record and Personnel Office, the Faculty Salary Scales for 1967-1972, the Faculty Development Plan for 1970-1976, the Terminal Report of MSU's first president Dr. Antonio Isidro and Board Resolution No. 742 provided data. The yearly rate of turnover followed an irregular pattern with the highest rate (28.58 percent) in 1969. Faculty members with bachelors degrees have the highest turnover rate. The causes for leaving are the desire to pursue higher academic degrees and lack of faculty organization that establishes and protects faculty rights. Majority of the turnovers joined government offices for employment rather than private ones. Those who did not seek employment and did not go abroad pursued graduate or post graduate studies.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Universities and colleges -- Faculty